Legal Certainty in Employment Termination Protection for Permanent Workers in Outsourcing Companies: An Analysis of Industrial Relations Court Decision No. 267/Pdt.Sus-PHI/2022/PN.Jkt.Pst: Kepastian Hukum dalam Perlindungan Pemutusan Hubungan Kerja bagi Pekerja Tetap di Perusahaan Outsourcing: Analisis Putusan Pengadilan Hubungan Industrial Nomor 267/Pdt.Sus-PHI/2022/PN.Jkt.Pst - Setiadi, Margaretha Putri; Rasji, Rasji (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Outsourcing has become a prevalent labor practice in Indonesia, yet its implementation often creates legal uncertainty for permanent workers, particularly during termination of employment (PHK). Specific Background: The Industrial Relations Court (PHI) Decision No. 267/Pdt.Sus-PHI/2022/PN.Jkt.Pst highlights inconsistencies in applying normative protections for outsourced workers following unilateral termination by PT G4S Security Services. Knowledge Gap: Despite existing regulations and judicial guidelines such as SEMA No. 3/2015, limited studies examine the judicial deviation from these norms and its implications for legal certainty and substantive justice. Aims: This study analyzes judicial reasoning behind the non-application of SEMA No. 3/2015 and assesses its juridical consequences for worker protection in the outsourcing system. Results: Findings indicate that the judges prioritized substantive justice by granting full process wages and reinstatement, deviating from the six-month wage limit mandated by SEMA. Novelty: The study offers a comparative analysis between the PHI decision and Supreme Court Decision No. 393 K/Pdt.Sus-PHI/2024, revealing structural inconsistency in enforcing legal certainty. Implications: These inconsistencies highlight the urgent need to harmonize judicial guidelines and strengthen regulatory protections to ensure fairness and clarity for outsourced workers. Highlights: Emphasizes the tension between substantive justice and legal certainty in PHK cases for outsourced permanent workers. Highlights judicial deviation from SEMA No. 3/2015, especially regarding the six-month limit on process wages. Shows the need to harmonize regulations and judicial guidelines to strengthen protection for outsourced workers. Keywords: Legal Protection, Permanent Workers, Outsourcing, Termination of Employment, Legal Certainty